2017
DOI: 10.1007/s11625-017-0470-0
|View full text |Cite
|
Sign up to set email alerts
|

Towards systemic and contextual priority setting for implementing the 2030 Agenda

Abstract: How the sustainable development goals (SDGs) interact with each other has emerged as a key question in the implementation of the 2030 Agenda, as it has potentially strong implications for prioritization of actions and their effectiveness. So far, analysis of interactions has been very basic, typically starting from one SDG, counting the number of interactions, and discussing synergies and trade-offs from the perspective of that issue area. This paper pushes the frontier of how interactions amongst SDG targets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
443
2
12

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 411 publications
(466 citation statements)
references
References 29 publications
9
443
2
12
Order By: Relevance
“…Le Blanc [11,15] has already demonstrated that the SDGs are designed in such a fashion as to create interlinkages between the individual goals and form a complex network of goals (e.g., ref. [10], see Note 4). Positive interactions between SDGs outweigh trade-offs and counteracting effects between goals, which is favorable to facilitating policy coherence across policy domains.…”
Section: Clarifications On Data and Methodsological Proceduresmentioning
confidence: 99%
“…Le Blanc [11,15] has already demonstrated that the SDGs are designed in such a fashion as to create interlinkages between the individual goals and form a complex network of goals (e.g., ref. [10], see Note 4). Positive interactions between SDGs outweigh trade-offs and counteracting effects between goals, which is favorable to facilitating policy coherence across policy domains.…”
Section: Clarifications On Data and Methodsological Proceduresmentioning
confidence: 99%
“…This is exemplified by the case of Cape Town, where, as previously mentioned, alignments are being sought between the SDGs work and the elaboration of a resilience strategy. Weitz et al (2018) propose a systematic approach to assess the interactions of SDG targets by considering how progress in one target influences progress on another. They follow Nilsson et al's (2017) framework consisting of a seven-point typology which indicates the nature of the interaction of one target with others and whether the relationship is positive or negative.…”
Section: ) Trade-offs and Synergiesmentioning
confidence: 99%
“…McCollum et al () discuss Goal 7 (Energy) and its links in detail using the 7‐point scale introduced by Nilsson, Griggs, and Visbeck (). Weitz, Carlsen, Nilsson, and Skåanberg () select two targets per Goal and analyse directed linkages between these, drawing directly on the context of Sweden. Le Blanc, Freire, and Vierros () discuss SDG 14 (Oceans) and consider directed links both between the seven targets associated with Goal 14 and between these targets and the other Goals.…”
Section: Introductionmentioning
confidence: 99%